Pharmacometrics, Physiologically Based Pharmacokinetics, Quantitative Systems Pharmacology—What's Next?—Joining Mechanistic and Epidemiological Approaches. (9th June 2019) - Schmidt, Stephan; Kim, Sarah; Vozmediano, Valvanera; Cristofoletti, Rodrigo; Winterstein, Almut G.; Brown, Joshua D.
Abstract : The application of modeling and simulation (M&S) tools to biological, physiological, and clinical data has great potential to enhance drug development and regulatory decision making. The strategic development of multidisciplinary projects aimed at integrating methodologies from different disciplines may bridge between preclinical and clinical drug development as well as between academic curiosity and clinical practice. Herein we review the history and present the state of M&S approaches as well as our vision for future challenges and applications.